Answer:
A = 6
B = 3
C = 9
Explanation:
We start by using repeatedly the product rule of logarithms that converts the logarithm of a product of two factors into the addition of logarithms:
:
![log (x^6*y^3*z^9)= log (x^6*[y^3*z^9])=log(x^6)+log(y^3*z^9)=\\=log(x^6)+log(y^3)+log(z^9)](https://img.qammunity.org/2020/formulas/mathematics/college/1octrca263eo07phf3ycjvmkwjhgp6lix1.png)
At this point we use on each term of the expression we found above, the power rule of logarithms that states:
![log(A^m)=m*log(A)](https://img.qammunity.org/2020/formulas/mathematics/college/865lij48t5fj4v7yfbu78t99kshajnloa1.png)
This gives as:
![log(x^6)+log(y^3)+log(z^9)=6*log(x)+3*log(y)+9*log(z)](https://img.qammunity.org/2020/formulas/mathematics/college/p1142d5am1nw3wfsh3y27regbpzq52opji.png)
Therefore, the coefficients A, B, and C requested are:
A = 6
B = 3
C = 9